2017
DOI: 10.1177/1475921716688166
|View full text |Cite
|
Sign up to set email alerts
|

Bridge extreme stress prediction based on Bayesian dynamic linear models and non-uniform sampling

Abstract: Bridge monitoring systems produce a large amount of data, including uniform and non-uniform sampled data in the long-term service periods; the proper handling of these data is one of the main difficulties in structural health monitoring. To properly predict structural non-uniform extreme stress and deal with the uncertainties of the monitored data, the objectives of this article are to present (a) Bayesian dynamic linear models about non-uniform extreme stress, (b) monitoring mechanism about the Bayesian dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Wang and his colleagues 30 handle SHM issues under BDLM framework, where time-dependent structural response was modeled through the separation of subcomponents, with the model parameters estimated utilizing an expectation maximization (EM) algorithm. [31][32][33] Fan 34 predicted the nonuniform extreme stress of I-39 Northbound Bridge in the USA using BDLM with the secondorder polynomial and showed that the predicted extreme stress was basically consistent with the observations. Liu 35 proposed a BDLM framework based on the cubic function to select the optimal probability distribution function of the initial stress state to predict the extreme stress of the structure effectively.…”
Section: Introductionsupporting
confidence: 56%
“…Wang and his colleagues 30 handle SHM issues under BDLM framework, where time-dependent structural response was modeled through the separation of subcomponents, with the model parameters estimated utilizing an expectation maximization (EM) algorithm. [31][32][33] Fan 34 predicted the nonuniform extreme stress of I-39 Northbound Bridge in the USA using BDLM with the secondorder polynomial and showed that the predicted extreme stress was basically consistent with the observations. Liu 35 proposed a BDLM framework based on the cubic function to select the optimal probability distribution function of the initial stress state to predict the extreme stress of the structure effectively.…”
Section: Introductionsupporting
confidence: 56%
“…Usually, the relationship between each explanatory variable and the response variable should be solved at first. The abovementioned linking mechanism can be defined as generalized linear and non-linear models [ 26 , 44 ], of which the first one has a simpler structure and can be adopted by a wide range of problems. In this study, we establish the linear regression model through the mean response variable given the explanatory variables.…”
Section: Dynamic Bayesian Networkmentioning
confidence: 99%
“…29 ARMA models can be formulated using state-space equation as dynamic linear models (DLMs), and these models include regression, trend, seasonality and AR components within a single formulation to account for the environmental and operational effects. 29,40,41,43 Bayesian formulation of such models, BDLMs, have become increasingly popular in recent years for modelling static time-series data such as extreme stresses 41 and TIS. 29 While BDLM/DLM are the most generalised formulation, the complex task of variance and co-variance matrix conversion restricts the number of parameters that can be included in these models.…”
Section: Introductionmentioning
confidence: 99%